Evaluating Nahwu Teaching Materials in Islamic Higher Education: Lecturer and Student Perceptions - Noza Aflisia; Abdiel Faiz Abbasyah; Jilan Jauza; Erda Anggelia (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2026)
The evaluation of Nahwu teaching materials in Islamic State Higher Education Institutions requires further attention, particularly regarding their alignment with the demands of twenty-first-century learning and educational technology development. Therefore, this study aims to evaluate the Nahwu teaching materials used in Arabic Education Study Programs at Islamic State Higher Education Institutions in Bengkulu Province based on lecturers’ and students’ perceptions. A mixed methods approach with an embedded design was employed, utilizing questionnaires as the primary data source and documentation as supporting data. The respondents consisted of 4 Nahwu lecturers and 251 students from IAIN Curup and UIN Fatmawati Sukarno Bengkulu. The results indicate that 62.50% of lecturers and 48.36% of students perceived the existing Nahwu teaching materials as less appropriate or inappropriate. Most materials are classical textbooks published no later than 2011 and lack integration with Education 4.0 and 5.0 learning technologies. Although some materials support grammatical comprehension, limitations in innovation, learning motivation, and higher-order thinking skills remain evident. Therefore, this study recommends developing more adaptive, contextual Nahwu teaching materials integrated with the TPACK framework to enhance effective learning in this Institutions